2010
DOI: 10.1042/cs20100174
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of habitual aerobic exercise on brachial artery flow-mediated dilation in middle-aged and older adults

Abstract: Brachial artery flow-mediated dilation (FMD) is impaired with aging and is associated with increased risk for cardiovascular disease (CVD). We determined if regular aerobic exercise improves brachial artery FMD in middle-aged/older (MA/O) men and postmenopausal women. In sedentary MA/O adults (age 55 – 79 years) without CVD, 8 weeks of brisk walking (6 days/week for ~50 min/day; randomized, controlled design) increased treadmill time ~20% in both MA/O men (n=11) and postmenopausal women (n=15) (P<0.01), withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
252
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(276 citation statements)
references
References 48 publications
18
252
6
Order By: Relevance
“…28 Collectively, these findings indicate that estrogen status plays a key permissive role in the adaptive response of the vasculature to exercise training in women. However, the studies in which beneficial vascular effects of exercise training were not observed in late postmenopausal women were characterized by low to moderate exercise intensities, 15,28 whereas high-intensity aerobic training such as that introduced in the current study has been shown to be associated with improvements in vascular function. 29 As this latter training modality has superior cardiovascular effects compared with moderate intensity exercise in patients with heart failure, 30 it may be that exercise intensity is an essential factor for reversing vascular dysfunction in postmenopausal women.…”
Section: Hypertensionmentioning
confidence: 93%
See 2 more Smart Citations
“…28 Collectively, these findings indicate that estrogen status plays a key permissive role in the adaptive response of the vasculature to exercise training in women. However, the studies in which beneficial vascular effects of exercise training were not observed in late postmenopausal women were characterized by low to moderate exercise intensities, 15,28 whereas high-intensity aerobic training such as that introduced in the current study has been shown to be associated with improvements in vascular function. 29 As this latter training modality has superior cardiovascular effects compared with moderate intensity exercise in patients with heart failure, 30 it may be that exercise intensity is an essential factor for reversing vascular dysfunction in postmenopausal women.…”
Section: Hypertensionmentioning
confidence: 93%
“…In a study on middle-aged and older adults, regular physical activity was found to improve flow-mediated dilation in previously sedentary men but not in late postmenopausal women. 15 In another study, flow-mediated dilation was increased in late postmenopausal women who had undergone 12 weeks of estradiol therapy before initiation of exercise training and continued treatment throughout the intervention period, whereas flow-mediated dilation did not change in the women receiving placebo. 28 Collectively, these findings indicate that estrogen status plays a key permissive role in the adaptive response of the vasculature to exercise training in women.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, aerobic exercise improves brachial artery flow-mediated dilatation in older males and females with low oestrogen but not women treated with oestrogen supplementation 184,187,188 . This suggests that oestrogen may be permissively involved in the beneficial effects of aerobic exercise on endothelial function in women 184 .…”
mentioning
confidence: 99%
“…Using continuous electronic heart rate and speed monitoring, we were able to show dose-response relationships in improving aerobic fitness. Similar to community-based studies of self-administered aerobic walking exercise in healthy people, 33 our intervention was conducted in a real-life environment, and is likely to generalize to community dwelling, independently ambulating patients with PD without significant comorbidities.…”
mentioning
confidence: 99%